Explaining the Factors Affecting the Relative Value of Services and Their Role in the Performance-Based Payment System in Teaching-Therapeutic Centers in the Six national-Wide region of the Country - Reza Shami; Darush Golamzadeh; Ahmad Vedadi (Zanjan University of Medical Sciences and Health Services, 2021)
Background: Pay for performance (P4P) is one of the most important issues in the health systems that promotes clinical quality, productivity, and patient satisfaction. Objectives: The current study aimed to identify and explain factors affecting the relative value of services and applying them in P4P in Iranian teaching-therapeutic centers. Methods: The current study was performed following a thematic analysis framework with an interview technique. The study population consisted of P4P experts in the six national-wide region of the country. Participants were selected using the purposeful and gradual sampling technique. Sampling was stopped upon reaching data saturation (i.e. 11 participants). Lincoln and Guba's evaluation method was used to determine reliability and validity. Qualitative data were analyzed using Nvivo version 12. Results: In total 13 basic themes and two organizer themes (i.e. technical and professional components) were identified regarding the factors affecting the relative value of health care services. Seven important elements in determining the professional component of the relative value of services included required time to perform the service, stress, knowledge, skill, experience, risk, as well as difficulty and complexity of the service. Conclusion: The model developed in the present study can be used to determine the total relative value of each service and setting tariff of medical services provided by health staff, including nurses.